Upaya Guru dalam Meningkatkan Mutu Pembelajaran Agama Islam Melalui Ulangan Harian di Sekolah SMP Negeri 3 Surakarta - Ike Yuliani; Santi Nurul Putri M; Aji Satrio K (STIKes Ibnu Sina Ajibarang, 2023)
Religion plays a central role in the lives of Indonesian society, being a strong foundation from birth to death, so that secular ideology has difficulty developing because of its connection with religious awareness. Religious education in Indonesia has an important role in forming characters with noble and competitive morals. Even though we are faced with a religious learning crisis, investment in improving the quality of religious education in all schools in Indonesia is important. This study tries to evaluate efforts to improve the quality of Islamic learning at SMP Negeri 03 Surakarta, with a focus on implementing daily tests. Interview results show that daily tests are carried out twice every half semester, despite tight schedule constraints. Even though students show a positive increase in grades during the implementation of the independent curriculum with a practical approach, daily tests which are more theoretical in nature are less popular. However, efforts to improve the quality of religious learning in schools involve drilling activities, independent tutoring, and peer assistance for students who have not reached the target. Regular evaluation and constructive feedback are key in increasing students' understanding of religious values. This research also looks at curriculum development strategies and the use of technology in improving the quality of religious learning. In conclusion, investment in Islamic education is not only the development of spirituality, but also an important contribution in forming a generation that can contribute positively to the progress of society.